Observations of a variety of drainage patterns in bamboo foams - WEAIRE, DENIS LAWRENCE; HUTZLER, STEFAN (EDP Sciences, 2008)
We have explored the patterns of drainage in a bamboo foam, i.e. a foam consisting of an arrangement of parallel soap films with equidistant spacing. We find an intriguing variety of such patterns, both static and dynamic. All involve the formation of drainage channels at the wall of the column, which are variously arranged and in some cases rotating and oscillating.
PUBLISHED
Keywords: Physics